Early effects of high cholesterol diet on the kidney of an animal model - Hamad Mohamed, Zenab B.; Hamad Alfarisi, Hamad Abdulsalam; Abdullah, Nor Zamzila; Harun, Norra; Muhammad, Naznin; Abdul Rahim, Roslina (PONTE Editore, 2018)
BACKGROUND: Previous studies have proven that there exists a complex association between progressive kidney damage and hypercholesterolemia. Most of them focused on the impact of chronically high blood cholesterol levels on the kidney. Information on the early effects of hypercholesterolemia on the kidney is still lacking. The aim of this study is therefore to determine early effects of high cholesterol diet on the kidney in an animal model. METHODOLOGY: Ten female Sprague-Dawley rats were divided into two groups: the control group, fed with commercial rat pellet and the high cholesterol diet (HCD) group, fed with 12% cholesterol diet with 0.3% cholic acid. Biochemical analysis of the lipid profile and renal function were performed at completed 48 hours, 7 days, and 6 weeks of the experiment. The animals were sacrificed at 6 weeks and the kidneys were harvested for histological examination. RESULTS: The HCD group rats had significantly higher levels of serum total cholesterol (at 7 days and 6 weeks). The HDL-c and triglyceride levels were, however lower at 6 weeks. The mean serum creatinine level of the HCD group was increased after 48 hours and 7 days compared to control group. Histological examination of the kidney tissue of the HCD group at 6 weeks revealed segmental mesangial hypercellularity and mesangial matrix expansion of the glomeruli. CONCLUSION: The 12% cholesterol diet induced dyslipidaemia in the animal model. It resulted in acute kidney injury based on the serum creatinine at 48 hours and also 7 days. Kidney tissues examined at 6 weeks revealed changes confined to mesangial cells of the renal glomeruli.